Sambajo: Sambal Sasak Bajo Untuk Meningkatkan Ekonomi Kreatif. - Azizah, Nusrotun; Kusuma, Anindita Suliya Hangesti Mandra; Aini, Miftahul; Karima, Maulidia; Albaniah, Melly; Azlin, Nirma Holis; Febriadi, Dani; Nuraini, Zun (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Fish is a food source of animal protein needed by humans. Every year the need for this protein source continues to increase along with the growth of the world population. With the increasing production and demand for fish, post-harvest handling is needed, namely preservation. One of the easiest ways of preserving is by salting or commonly known as salted fish. The high level of public consumption of salted fish and the potential for development as a local food product. SAMBAJO is here as an innovation in the culinary field and to improve the creative economy. This product is a typical Sasak chili sauce mixed with salted fish or bajo in Sasak language. This product produced by PKM-Kewirausahaan has advantages compared to products already on the market, namely using typical Sasak chili sauce which has the potential to be popular with the local community. Sambajo started production on November 7 2023 and was marketed on November 13 2023. We adjusted 20 bottles of this production of chili sauce once in this initial stage according to the sales location and according to consumer orders and sold it at a price of IDR. 15,000.